Application of the Internet of Things in Waste Processing Equipment for Batik Craftsmen in Iroyudan Village, Guwosari Village, Pajangan District, Bantul Regency - Liya Yusrina Sabila; Shinta Amelia; Rachma Tia Evitasari; Shandy Auliya Ma'arief; Pita Adis Hernanda (UKInstitute, 2024)
Yogyakarta is one of the largest batik-producing cities in Indonesia. It has a positive impact on the artisans's economy. It adds new jobs, but this has yet to be matched by the skills and knowledge of the artisans in managing liquid waste generated from batik activities. So far, liquid batik waste has been stored in holding tanks and allowed to seep into the ground or even directly thrown into the water without further processing. So, it harms the environment, such as pollution of the waters and the surrounding environment and even the death of aquatic biota. Therefore, a renewable technological innovation was created, combined with the Heterogeneous Fenton method as a medium for processing batik waste. The methods used include pre-test, lecture, question and answer and post-test. Based on service activities that have been carried out, including providing information on equipment technology of batik waste processing to batik artisans in Desai Iroyudan, Guwosari Village, Pajangan District, Bantul Regency, Yogyakarta, it is known that the level of community understanding has become 98% or increased by 23%.